PENGARUH KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - ERIKA DEWI, NESIA; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
This research aims to identify and provide empirical evidence of the influence of the independent variables and the audit committee of institutional ownership and control variables firm size and leverage to earnings management in a manufacturing company. The samples are manufacturing companies listed in Indonesia Stock Exchange. The sample selection using purposive sampling technique during the study period from 2014 to 2016 year. Data were analyzed using linear regression. The results showed that the audit committee and institutional ownership has no effect on earnings management, while the results of the control variables firm size and leverage positive effect negative effect on earnings management. Keywords : earnings management, audit committees, institutional ownership.